2016
DOI: 10.2109/jcersj2.16123
|View full text |Cite
|
Sign up to set email alerts
|

Molecular routes syntheses of graphite-like C–N compounds with various N/C ratios in high pressure and temperature

Abstract: Graphite-like carbon nitride inorganic compounds were synthesized from molecular 1,2,4-triazole C 2 N 3 H 3 in high pressure and temperature conditions using a DIA-type multianvil large press. It was found that the N/C content ratio of the carbon nitrides can be systematically controlled by changing the heating temperature at 5 GPa. The substitution of nitrogen for carbon in graphene layers results in the low crystallinity of the synthesized CN compounds. It should be noted that the c-axis which is equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…The typical diffraction peak at around 27° has also been found in other nitrogendoped graphene or graphite materials. In fact, Horibe et al reported that this interplanar distance decreases monotonously with increasing N/C content ratio [38,39]. According to Horibe's reports, an interplanar distance of 3.31 Å would correspond to an N/C atomic ratio close to 0.6, which is actually very close to the one found by X-ray photoelectron spectroscopy for the materials under study.…”
Section: X-ray Diffraction (Xrd) Measurementssupporting
confidence: 75%
See 1 more Smart Citation
“…The typical diffraction peak at around 27° has also been found in other nitrogendoped graphene or graphite materials. In fact, Horibe et al reported that this interplanar distance decreases monotonously with increasing N/C content ratio [38,39]. According to Horibe's reports, an interplanar distance of 3.31 Å would correspond to an N/C atomic ratio close to 0.6, which is actually very close to the one found by X-ray photoelectron spectroscopy for the materials under study.…”
Section: X-ray Diffraction (Xrd) Measurementssupporting
confidence: 75%
“…9) and by elemental quantification of the carbon, nitrogen and oxygen contents ( Table 1). respectively [39][40][41][42][43][44][45], and relative weight percent (wt%) values are presented in Table 3.…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…Other nitrogen-doped graphene or graphitic materials also feature the diffraction peak at around 27°. In fact, Horibe et al found that the interplanar distance monotonously decreased as the N/C content ratio increased [26,27]. However, other factors must be considered, provided that in pure carbon materials the interplanar distance can vary from 3.37 to 3.50 Å depending on the degree of layer-ordered stacking.…”
Section: X-ray Diffraction Measurementsmentioning
confidence: 99%
“…Several HPHT experiments using large-volume presses, such as piston-cylinder apparatus, belt-type press, and multianvil press have also been performed. Various analytical methods such as X-ray diffraction measurements, Raman and infrared (IR) spectra, X-ray photoelectron spectroscopy, and transmission electron microscope with electron energy loss spectroscopy have been used to evaluate crystallinity, chemical compositions, and bonding of the reaction products. , It has been reported that the N/C ratio of carbon-nitride materials decreases with increasing temperature, in the case where synthesis focused on 1,2,4-triazole (C 2 N 3 H 3 ) and melamine (C 3 N 6 H 6 ) . Graphitic C 3 N 4 decomposed into diamond and probably N 2 above 1073–1173 K at 22–25 GPa .…”
Section: Introductionmentioning
confidence: 99%